Tradition et changement phonétique dans une variété de contact : l’anglais de Lewis et Harris - Stephan Wilhelm (Corela)
From a grammatical and lexical point of view, the variety of English spoken in the Outer Hebrides is akin to Standard Scottish English (SSE). From a phonetic and phonological point of view, however, it is absolutely distinctive, mainly because of the influence and interference of Scottish Gaelic.Based on two corpora composed of recordings of speakers from Lewis and Harris as well as on informal observations collected in the Outer Hebrides during the past sixteen years, this paper identifies and describes the most salient traits of traditional Hebridean accents, be they segmental or prosodic.A brief examination of the speech of Hebridean adolescents highlights several changes in progress. These are to be traced both from the diffusion of individual phonetic innovations and from the attrition of marked variants – a phenomenon known as dialect levelling. These changes seem to be facilitated both by the decline of the Gaelic language and by the rejection of the traditional Hebridean values by a number of young speakers. Using data collected from adolescents as well as informal observations, we try to identify some of the most prominent changes that affect the accents of Lewis and Harris in apparent time.